Occurrence of Scutellonema bradys on yam in Benin - Baimey, H.; Coyne, Danny L.; Labuschagne, N. (2006)
Scutellonema bradys is the major nematode species that affect yam (Dioscorea spp.) production and storage in Benin. A nematode survey was conducted during the storage periods of 2002and 2003 in the yam-growing areas to study the distribution, population diversity and incidence of S. bradys on tubers marketed in Benin. The proportion of tubers infected with S. bradys varied between yam cultivars and species as well as the origin of tubers. Kokoro and D. rotundata were, respectively, the yam cultivar and species most frequently observed with symptoms of S. bradys damage. Higher nematode densities were found on D. rotundata than on D. cayensis and D. alata. Yoruba Dundu was most highly infected. Higher densities of S. bradys were recovered from tubers occurring in the southern Guinea Savannah agro-ecological zone compared to tubers from the northern Guinea Savannah. Molecular studies on nematodes extracted from yam tubers showed high levels of polymorphism. Three nematode isolates selected from geographically different localities showed different levels of pathogenicity on yam in the field and during storage.